(untitled) (Tanzania Medical Journal, 2023)
Neurofibromatosis type I (NF1) is an autosomal dominant genetic condition caused by germline and sometimes somatic NF1 gene mutations. Skin lesions, skeletal deformities, peripheral neurofibromas, central nervous system tumors, and behavioral abnormalities are some of the phenotypic manifestations of the condition. We present a case of a child diagnosed with NF1 who had cutaneous lesions from birth and plexiform neurofibromas for a year, as well as a newly reported variant of the NF1 gene mutation. A three-year-old female infant appeared with generalized hyperpigmented skin lesions that had been present since birth, as well as a one-year history of right facial edema. Physical and radiological examination revealed café-au-lait macules on the face, trunk, and lower limbs; right facial edema with ipsilateral ptosis and proptosis; plexiform neurofibromas involving the right cranial nerves III, IV, and V. As a result, the clinical criteria for NF1 diagnosis were met. In our context, the right face plexiform neurofibroma was inoperable, thus the patient was scheduled for palliative treatment and observation. Again, genetic testing to add to the diagnostic criteria for NF and determine the type of NF1 gene took months because the sample had to be sent abroad (Germany) for the confirmatory gene type test. The discovery of an NF1 gene mutation with heterozygous exon 31-36 deletion is highly unusual. The dearth of experienced people and diagnostic facilities at primary and secondary health care delivery and initial care centers resulted in a lack of anticipatory screening and timely intervention, resulting in delayed suspicion and diagnosis of NF1. Furthermore, the complex and costly logistics of coordinating and performing confirmatory genetic analysis abroad is a major barrier to the diagnosis and comprehensive care of this and other genetic-linked illnesses in developing nations.